Legal Standing Of Statement Letters In Proofing Cases Of Joint Property (Civil Case Study Number: 390/Pdt.G/2021/PA.Psp) - Pulungan, Nina Arnita; Syahnan, Mhd; Siregar, Ramadhan Syahmedi (Universitas Islam Sultan Agung, 2023)
This research aims to describe the position of the Statement Letter in Proving Joint Assets at the Padangsidimpuan Religious Court (Civil Case Study Number: 390/PDT.G/2021/PA.PSP) based on the Subekti Theory of Evidence and the Theory of Justice according to Islamic views. The type of research used is normative juridical with a qualitative approach method. Data collection techniques were carried out using observation, interviews and documentation techniques. The data analysis technique applies the theory of Miles, Huberman, & Saldana (2014). The results of this research are based on the theory of Evidence according to Subekti, that Evidence is to convince the judge about the truth of the argument or arguments put forward in a dispute. Thus, Parwit Simamora, who has submitted a statement letter, has promised the judge the truth of what he has stated in the letter through the answers ]he has submitted. So the panel of judges gave consideration and assessed that the position of the statement letter was proof of commencement which must be supported by other evidence. Meanwhile, the other witnesses who wrote the statement were not present in court to provide evidence, so they could not promise the judge what was stated in the statement because they did not fulfil the judge's invitation to appear in contradiction to stating their evidence so that the judge considered the position of the statement was not can be used as initial evidence as an initial backup or clue to the object of the case.